Karakteristik Permukiman Kota yang Memiliki Potensi Usaha Berbasis Rumah Tangga - Ima Rahmawati Sushanti; Intan Savia Fitri; Febrita Susanti (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2021)
Urban settlement is a built environment in an urban area that plays a role in determining the structure and identity of the city. The urban settlement area is currently not only used as a residence equipped with facilities and infrastructure to meet the living needs of the residents who live in it, but also to meet their economic needs. Urban settlements have certain characteristics based on the community and activities in them so that they can become the identity of the area. The existence of the Mutiara, Gold and Silver industrial clusters in Sekabela sub-district, Mataram city has implications for the surrounding settlements, both in economic, environmental and social aspects. The emergence of slum settlements in the residences around the Pearl, Gold and Silver industry causes less optimal representation of the area as a shopping tourism area. This study aims to determine the characteristics of settlements with household-based business potential and development strategies. The method used in this research is descriptive qualitative with primary and secondary data collection and analysis of Strength, Weakness, Opportunity and Threat. The results showed that the characteristics of the settlement were based on physical characteristics, namely: building layout, housing, facilities and infrastructure as well as the environment and non-physical characteristics, namely: the community and the activities that took place in it. The area development strategy based on settlement characteristics is in quadrant IV, namely the Competitive Strategy. Efforts are being made to improve the visual quality or image of the area, diversify the business and develop markets.